Implementation of a lecturer agenda management application using the scrum method at UIN Jurai Siwo Lampung - Krisna Widatama (Universitas Mercu Buana Yogyakarta, 2025)
Lecturers at UIN Jurai Siwo Lampung faced significant challenges in schedule management due to the lack of a centralized system, leading to frequent agenda conflicts and coordination inefficiencies. This research aimed to develop a functional agenda management application and evaluate the effectiveness of the Scrum method in this context. The software development process utilized the Scrum framework, emphasizing iterative sprints to adaptively handle changing user requirements. The results showed that the developed application successfully minimized scheduling overlaps through automated conflict detection features. Additionally, the Scrum method proved effective in accelerating the development cycle and ensuring the product met specific user needs. This study contributes a practical solution for enhancing academic productivity and offers empirical insights into implementing Agile methodologies within educational institutions.